Knowledge and practice of universal precautions among health care workers in four national hospitals in Kabul, Afghanistan - Fayaz, Said Hafizullah; Higuchi, Michiyo; Hirosawa, Tomoya; Sarker, Mohammad Abul Bashar; Djabbarova, Zakhro; Hamajima, Nobuyuki (The Journal of Infection in Developing Countries, 2014)
Introduction: This study aimed to assess the knowledge and practice of health care workers (HCWs) towards universal precautions (UPs) and to look into any associations between knowledge and practice. Methodology:A cross-sectional study was undertaken between August and October 2012, involving 300 HCWs from four national public hospitals in Kabul, Afghanistan. A self-administered questionnaire assessing the knowledge and practice of UPs was used. Results: Among the 300 respondents, the mean knowledge score was 5.2 with a standard deviation (SD) of 1.5. On the practice score, the mean was 8.7 (SD = 2.2). A total of 90.6% and 70.8% of HCWs believed that UPs were necessary in contact with urine/feces and tears, respectively, although UPs are not necessary in these cases. On the other hand, 57.8% reported that they always recapped the needle after giving an injection, and 31.8% did not always change gloves in between patients. There were no associations between the knowledge and self-reported practice of UPs. Conclusions: The HCWs in Kabul had inadequate knowledge and poor practice of UPs. Training for HCWs is needed to encourage them to adhere to practice based on improved knowledge.